A Preliminary Inventory of Angiospermic Flora of Bagatipara Upazila, Natore, Bangladesh (Bangladesh Journal of Plant Taxonomy, 2024)
Preparation of the country's flora is very challenging until baseline information on the flora of all district or upazila is available.  The purpose of this inventory was to record angiosperm plant species available in the different habitats of Bagatipara upazila, which is located in the eastern part of Rajshahi district. The traditional taxonomic method was applied for plant sample collection in different seasons of the year 2022 and the identification of the collected samples. This research resulted in the recording of a total of 377 species in 92 families. Among them, 310 species were from Magnoliopsida, and 67 were from Liliopsida. Asteraceae and Poaceae were the leading families of Magnoliopsida and Liliopsida, respectively. One-fourth of the total plant species were exotic, and more than half were valuable medicinal species. Artocarpus lacucha, Bridelia stipularis, Callicarpa longifolia, Eranthemum pulchellum, Oroxylum indicum, Potentilla supina, Sterculia foetida, and Terminalia arjuna were locally found rare. Threats such as climate change, expansion of arable land and pisciculture, use of herbicides, over exploitation, clearing brushwood, and unplanned construction activities have been identified. The present study concludes that the floristic composition of this area is still rich, though the area is facing some threats. Therefore, we strongly recommend adopting effective and adequate measures for sustainable conservation and monitoring of the biodiversity of this area.Bangladesh J. Plant Taxon. 31(1): 155-172, 2024 (June)